PELATIHAN PEMBUATAN BAKSO IKAN DAN NUGGET IKAN PADA KELOMPOK NELAYAN TAHI PEOTOROA DESA PUASANA KECAMATAN MORAMO UTARA KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - Laode Muhamad Hazairin Nadia; La Ode Huli; La Ode Abdul Rajab Nadia; Nurmaladewi Nurmaladewi (Universitas Teuku Umar, 2021)
The group of fishermen Tahi Peotoroa is a group that manages fishing and aquaculture fisheries. The fishermen's catch has sold directly only in fresh form by the mothers of fishermen to the people in Puasana village. This is due to a lack of knowledge in processing fishery products, especially from fish. The aim of this community service activity was to improve the knowledge and skills of members group of fishermen Tahi Peotoroa in processing products of fish meatballs and fish nuggets to optimize the utilization of fish catches in the village of Puasana North Moramo District, South Konawe Regency, Southeast-Sulawesi Province. The target of this community service activity was enriching knowledge and skills for the group of fishermen puasana village in processing fish into processed fish meatballs and fish nuggets. The method was delivered by lecturing and training to make fish meatballs and fish nuggets. The result was that all participants were able to make fish meatballs and fish nuggets made from mackerel.